Determining Surgical Complications in the Overweight (DISCOVER): a multicentre observational cohort study to evaluate the role of obesity as a risk factor for postoperative complications in general surgery. Issue 7 (20th July 2015) - Nepogodiev, Dmitri; Chapman, Stephen J; Glasbey, James; Kelly, Michael; Khatri, Chetan; Drake, Thomas M; Kong, Chia Yew; Mitchell, Harriet; Harrison, Ewen M; Fitzgerald, J Edward; Bhangu, Aneel
Abstract : Introduction: Obesity is increasingly prevalent among patients undergoing surgery. Conflicting evidence exists regarding the impact of obesity on postoperative complications. This multicentre study aims to determine whether obesity is associated with increased postoperative complications following general surgery. Methods and analysis: This prospective, multicentre cohort study will be performed utilising a collaborative methodology. Consecutive adults undergoing open or laparoscopic, elective or emergency, gastrointestinal, bariatric or hepatobiliary surgery will be included. Day case patients will be excluded. The primary end point will be the overall 30-day major complication rate (Clavien-Dindo grade III–V complications). Data will be collected to risk-adjust outcomes for potential confounding factors, such as preoperative cardiac risk. This study will be disseminated through structured medical student networks using established collaborative methodology. The study will be powered to detect a two-percentage point increase in the major postoperative complication rate in obese versus non-obese patients. Ethics and dissemination: Following appropriate assessment, an exemption from full ethics committee review has been received, and the study will be registered as a clinical audit or service evaluation at each participating hospital. Dissemination will take place through national and local research collaborative networks.